Effects of Work Ethics and Job Satisfaction on Employee Performance Moderated by Leadership at RS Sarkies Aisyiyah Kudus - Affan Wazzar Achmad; Ahmad Mukhlisin; Izzah Sarirotun Nijwah (Value Added : Majalah Ekonomi dan Bisnis, 2026)
Employee performance plays an essential role in ensuring service quality and organizational sustainability in healthcare institutions. This study aims to examine the influence of work ethic and job satisfaction on employee performance with leadership as a mediating variable at RS Sarkies Aisyiyah Kudus. A quantitative research design was employed using a survey method involving 200 hospital employees as respondents. Data were collected through structured questionnaires and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS.The results show that work ethic and job satisfaction have positive and significant effects on leadership. In addition, work ethic, job satisfaction, and leadership each have positive and significant influences on employee performance. Mediation analysis further indicates that leadership significantly mediates the relationship between work ethic and employee performance as well as between job satisfaction and employee performance.The novelty of this study lies in empirically demonstrating the mediating role of leadership in strengthening the relationship between work ethic, job satisfaction, and employee performance in a hospital context in Indonesia. These findings highlight the importance of fostering a strong work ethic, enhancing job satisfaction, and strengthening leadership practices to improve employee performance in healthcare organizations.